Learning outcomes of the kindergarten teacher training programme in the light of students’ external practice (Training and Practice : Journal of Educational Sciences, 2021)
The University of Sopron Benedek Elek Faculty of Pedagogy worked out a research on learning outcomes of the kindergarten teacher training programme in cooperation with the Early Childhood Department of the Hungarian National College of Teachers. The gole of this study was exploring the experiences of our professional partners (kindergartens) on the challenges of the kindergarten teachers’ profession, including theoretical and methodological knowledge, readiness, learning outcomes and teaching requirements. Referring to the results it can be stated, that new, innovative learning outcomes, skills and contents are reqiured that increase the efficiency of kindergarten teacher training. strengthen practice-oriented training, support cooperative and reflective work, and develop students’ digital competencies.